Computational Tool for Fast in silico Evaluation of hERG K+ Channel Affinity - Chemi, Giulia; Gemma, Sandra; Campiani, Giuseppe; Brogi, Simone; Butini, Stefania; Brindisi, Margherita (Frontiers in Chemistry, 2017)
The development of a novel comprehensive approach for the prediction of hERG activity is herein presented. Software Phase has been used to derive a 3D-QSAR model, employing as alignment rule a common pharmacophore built on a subset of 22 highly active compounds (threshold Ki: 50 nM) against hERG K+ channel. Five features comprised the pharmacophore: two aromatic rings (R1 and R2), one hydrogen-bond acceptor (A), one hydrophobic site (H), and one positive ionizable function (P). The sequential 3D-QSAR model developed with a set of 421 compounds (randomly divided in training and test set) yielded a test set (Q2) equal to 0.802 and proved to be predictive with respect to an external test set of 309 compounds that were not used to generate the model (r2ext_ts = 0.86). Furthermore, the model was submitted to an in silico validation for assessing the reliability of the approach, by applying a decoys set, evaluating the Güner and Henry score (GH) and the Enrichment Factor (EF), and by using the ROC curve analysis. The outcome demonstrated the high predictive power of the inclusive 3D-QSAR model developed for the hERG K+ channel blockers, confirming the fundamental validity of the chosen approach for obtaining a fast proprietary cardiotoxicity predictive tool to be employed for rationally designing compounds with reduced hERG K+ channel activity at the early steps of the drug discovery trajectory.